The impact of HIV-1 subtypes on virologic and immunologic treatment outcomes at the Lagos University Teaching Hospital: A longitudinal evaluation - Ogbenna, AA; Meloni, S; Inzaule, S; Hamers, RL; Sigaloff, K; Osibogun, A; Adeyemo, TA; Okonkwo, P; Samuels, JO; Kanki, PJ; Rinke de Wit, TF; Akanmu, AS (Public Library of Science, 2019)
Introduction HIV is a highly diverse virus with significant genetic variability which may confer biologic differences that could impact on treatment outcomes.